Burden of Surgical Conditions in Uganda: A Cross-sectional Nationwide Household Survey. Issue 2 (August 2017) - Tran, Tu M.; Fuller, Anthony T.; Butler, Elissa K.; Makumbi, Fredrick; Luboga, Samuel; Muhumuza, Christine; Ssennono, Vincent F.; Chipman, Jeffrey G.; Galukande, Moses; Haglund, Michael M.
Abstract : Objective: To quantify the burden of surgical conditions in Uganda. Background: Data on the burden of disease have long served as a cornerstone to health policymaking, planning, and resource allocation. Population-based data are the gold standard, but no data on surgical burden at a national scale exist; therefore, we adapted the Surgeons OverSeas Assessment of Surgical Need survey and conducted a nation-wide, cross-sectional survey of Uganda to quantify the burden of surgically treatable conditions. Methods: The 2-stage cluster sample included 105 enumeration areas, representing 74 districts and Kampala Capital City Authority. Enumeration occurred from August 20 to September 12, 2014. In each enumeration area, 24 households were randomly selected; the head of the household provided details regarding any household deaths within the previous 12 months. Two household members were randomly selected for a head-to-toe verbal interview to determine existing untreated and treated surgical conditions. Results: In 2315 households, we surveyed 4248 individuals: 461 (10.6%) reported 1 or more conditions requiring at least surgical consultation [95% confidence interval (CI) 8.9%–12.4%]. The most frequent barrier to surgical care was the lack of financial resources for the direct cost of care. Of the 153 household deaths recalled, 53 deaths (34.2%; 95% CI 22.1%–46.3%) were associated with surgically treatable signs/symptoms. Shortage of time was the most frequently cited reason (25.8%) among the 11.6% household deaths that should have, but did not, receive surgical care (95% CI 6.4%–16.8%). Conclusions: Unmet surgical need is prevalent in Uganda. There is an urgent need to expand the surgical care delivery system starting with the district-level hospitals. Routine surgical data collection at both the health facility and household level should be implemented.